Finite element analysis and optimization of foam filled fender under quasi static and dynamic responses - Djamaluddin, F. (Frontiers in Mechanical Engineering, 2023)
Mainly composed of elastic materials, ship fenders are utilised on all kinds of vessels for the protection of berthing structures and the prevention of damage due to heavy crash loads. This study aims to enhance deformation mode and crash performance of foam-filled fenders under quasi-static and dynamic loadings. Six models of ship fender’s structure are chosen for simulation test. The fenders are examined for crashworthiness parameters such as crushing force efficiency (CFE) and specific energy absorption (SEA). Finite element analysis is conducted for estimating crash responses then compared to an appropriate reference and experiment result. Four design variables are considered for instance height, foam density, thickness, and material for optimization. Non-dominated Sorting Genetic Algorithm II as multi-objective optimization approach are used to obtain the maximum of Specific Energy Absorption (SEA) and the minimum of Crushing Force Efficiency (CFE). Based on the results of the optimization, the best performance is observed in model 5, however it can be replaced the traditional fender design.